2011
DOI: 10.1159/000327399
|View full text |Cite
|
Sign up to set email alerts
|

Role of Circadian Neuroendocrine Rhythms in the Control of Behavior and Physiology

Abstract: Hormones play a major role in regulating behavior and physiology, and their efficacy is often dependent on the temporal pattern in which they are secreted. Significant insights into the mechanisms underlying rhythmic hormone secretion have been gained from transgenic rodent models, suggesting that many of the body’s rhythmic functions are regulated by a coordinated network of central and peripheral circadian pacemakers. Some neuroendocrine rhythms are driven by transcriptional-posttranslational feedback circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 207 publications
(111 reference statements)
2
25
0
Order By: Relevance
“…10,11,14 As expected, when we administered T to the old animals, their plasma T levels increased to young levels within an hour of oral administration. Due to the relatively high clearance rate of testosterone, this elevation was not sustained throughout the night; however, plasma levels of dihydrotestosterone (DHT), the more active metabolite of T, closely resembled that of young males after T administration (data not shown).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…10,11,14 As expected, when we administered T to the old animals, their plasma T levels increased to young levels within an hour of oral administration. Due to the relatively high clearance rate of testosterone, this elevation was not sustained throughout the night; however, plasma levels of dihydrotestosterone (DHT), the more active metabolite of T, closely resembled that of young males after T administration (data not shown).…”
Section: Introductionsupporting
confidence: 78%
“…Similarly, we suspended the DHEA in sesame oil (2 mg/mL) and mixed it with chocolate or placed it inside a cookie. Our preliminary studies indicated that a single administration of DHEA failed to produce a sustained elevation of circulating DHEAS, confirming that the single-dose DHEA paradigm used in the premenopausal females was not ideal at reproducing the sustained elevation of DHEAS that is typically observed in young animals 9,10 ; in contrast, the plasma DHEAS levels resulting from the new doubledose DHEA supplementation paradigm closely followed those of the young control males.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Some, as blood pressure levels, heart rate, lipid profile, insulin and cortisol serum levels are also factors associated to the development of many diseases and cardiovascular events (5)(6)(7)(8)(9). Seasonal changes on type 1 diabetes incidence have also been reported in literature, with new onset cases diagnosed more commonly during winter months (10).…”
Section: Introductionmentioning
confidence: 97%
“…These rhythms have a period of approximately 24 h and are regulated by a highly coordinated circadian neuroendocrine mechanism that comprises three major components: (1) photoreception by the retina and transmission of neural signals along the retinohypothalamic tract, (2) integration of photoperiodic information with an internal reference circadian pacemaker located in the suprachiasmatic nucleus (SCN) of the hypothalamus, and (3) dissemination of synchronized circadian information to target organs, via the autonomic nervous system and through humoral pathways, and integration with local oscillator circuits (Okamura 2004;Karatsoreos and Silver 2007;Maywood et al 2007;Mendoza and Challet 2009;Bonnefont 2010;Urbanski 2011b). When functioning correctly, this mechanism ensures that various internal biochemical processes are compartmentalized not just spatially but also temporally and that physiological functions and behaviors occur at an appropriate time of day (Lemos et al 2006;Kalsbeek et al 2006).…”
Section: Introductionmentioning
confidence: 99%